2005
DOI: 10.1348/026151005x26075
|View full text |Cite
|
Sign up to set email alerts
|

Minority children's intergroup attitudes about peer relationships

Abstract: Intergroup attitudes were assessed in African‐American (N=70) and non‐African‐American minority (N=80) children, evenly divided by gender, in first (M=6.5 years old) and fourth (M=9.6 years old) grades attending mixed‐ethnicity public schools in a suburban area of a large mid‐Atlantic city in the USA. Children were interviewed to test hypotheses about implicit racial biases, perceptions of similarity between peer dyads, and judgments about cross‐race friendships. Implicit racial biases emerged when children ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 17 publications
6
48
2
1
Order By: Relevance
“…A study with European-American students at 1 st and 4 th grades in homogeneous schools found that European-American students were more likely to attribute negative intentions to minority students than to majority students in ambiguous interracial peer dyadic situations (McGlothlin & Killen, in press). In contrast, minority and majority students in 1 st and 4 th grades in heterogeneous schools were unlikely to use race to make attributions of intentions (Margie et al, 2005;McGlothlin, Killen, & Edmonds, 2005a). However, by 4 th grade, European-American students at both schools were less likely to expect that cross-race peer dyads could be friends than were minority students, suggesting that racial biases about friendships exist as early as 4 th grade.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A study with European-American students at 1 st and 4 th grades in homogeneous schools found that European-American students were more likely to attribute negative intentions to minority students than to majority students in ambiguous interracial peer dyadic situations (McGlothlin & Killen, in press). In contrast, minority and majority students in 1 st and 4 th grades in heterogeneous schools were unlikely to use race to make attributions of intentions (Margie et al, 2005;McGlothlin, Killen, & Edmonds, 2005a). However, by 4 th grade, European-American students at both schools were less likely to expect that cross-race peer dyads could be friends than were minority students, suggesting that racial biases about friendships exist as early as 4 th grade.…”
Section: Discussionmentioning
confidence: 81%
“…For example, investigations of attributions of intention using ambiguous pictures have revealed that while majority and minority children make similar judgments about attributions of intention (with some qualifications as described below), they have different viewpoints about the potential for cross-race relationships (Margie, Killen, Sinno, & McGlothlin, 2005;McGlothlin, Killen, & Edmonds, 2005b). Specifically, 6 and 9 year old minority students were more likely to judge that a cross-race dyad, depicted in a scenario, could be friends than did majority students (attending the same schools).…”
mentioning
confidence: 99%
“…Accordingly, White children and adolescents are less friendly (Hallinan & Teixeira, 1987), less intimate (Shelton et al, 2010, Stearns, Buchman, & Bonneau, 2009, and give less importance to their cross-ethnic peers (Pica-Smith, 2011) compared to ethnic minorities. Similarly, White majority group members tend to report higher same-ethnic friendship numbers (Clark & Ayers, 1992;Howes & Wu, 1990;Margie, Killen, Sinno, & McGlothlin, 2005;Shrum, Cheek, & Hunter, 1988) and lower levels of diversity in their friendship group compared to ethnic minorities (Fischer, 2008).…”
Section: Cross-ethnic Friendships Across Ethnic Groupsmentioning
confidence: 99%
“…These findings also suggest that engaging in similar conversations about race may be important for youth in traditional Scouting programs, especially given that these youth are typically from White, middle-class backgrounds, and may be less familiar with discussions of race, racism, and topics like the importance of inter-racial friendships, given their majority status (Leman & Lam, 2008;Margie et al, 2005). Preliminary analyses indicate that discussions of race-related topics have not occurred in interviews conducted with predominantly White, middle-class youth enrolled in traditional Scouting programs.…”
Section: Discussionmentioning
confidence: 92%